2011
DOI: 10.3171/2010.3.jns10427
|View full text |Cite
|
Sign up to set email alerts
|

Tibial intraneural ganglia at the ankle and knee: incorporating the unified (articular) theory in adults and children

Abstract: These cases detail the important features of intraneural ganglion cysts of the tibial nerve and document the clinical utility of incorporating the unifying (articular) theory for the surgical management of tibial intraneural ganglia in adults and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…To our knowledge, there are only 11 reported cases of pediatric peroneal intraneural ganglion cysts [2,3,12,13,14,15,16,17,18]. There are also about 18 cases of tibial intraneural ganglion cysts, and among them only 1 case is in the pediatric age group [19,21]. We think that our small case series of 4 patients is an important contribution to the current literature.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To our knowledge, there are only 11 reported cases of pediatric peroneal intraneural ganglion cysts [2,3,12,13,14,15,16,17,18]. There are also about 18 cases of tibial intraneural ganglion cysts, and among them only 1 case is in the pediatric age group [19,21]. We think that our small case series of 4 patients is an important contribution to the current literature.…”
Section: Discussionmentioning
confidence: 92%
“…This could be related to repeated minor trauma or to a more strenuous activity. Our literature review revealed that there have been only 11 reported cases of peroneal intraneural ganglion cysts in the pediatric age group [2,3,12,13,14,15,16,17,18], and only 1 case of pediatric tibial ganglion cyst has been reported so far [19]. In this study, we present our experience with peroneal and tibial intraneural ganglion cysts treated surgically in 4 pediatric patients to determine clinical, radiological, electrophysiological and surgical features as well as the clinical outcome of this rare entity in the pediatric age group.…”
Section: Introductionmentioning
confidence: 99%
“…Various case reports have described the involvement of tibial nerve in the popliteal fossa by the INGC[7,12,36,40,46,47]. These tibial INGCs are the posterior counterpart of the peroneal INGCs and demonstrate an intraneural cyst and its connection to the adjacent joint via the articular branch to the PTF joint[40,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…These tibial INGCs are the posterior counterpart of the peroneal INGCs and demonstrate an intraneural cyst and its connection to the adjacent joint via the articular branch to the PTF joint[40,47,48]. In one of our cases there was evidence of dual communication of the tibial intraneural cyst to both the knee and PTF joint through its corresponding articular branches (Figures 3-5) and further extension of cyst into the popliteus and tibialis posterior nerve branches (Figures 3-5).…”
Section: Discussionmentioning
confidence: 99%
“…12 An intraneural ganglion of the tibial nerve is a rare type of tarsal tunnel ganglion that originates from neighboring joints with connections to the joints through articular branches. [13][14][15] It calls for open resection and is a contraindication for endoscopic ganglionectomy (Table 1).…”
mentioning
confidence: 99%